Value of Information for the Innovation of Vibration-Based Monitoring Systems for Multiple Applications - Costa, Giancarlo; Limongelli, Maria Pina ; 0000-0002-9353-5439; Thöns, Sebastian (11th International Conference on Experimental Vibration Analysis for Civil Engineering Structures, EVACES 2025, Porto, Portugal, 2025-07-02 - 2025-07-04, 2025)
The Value of Information from Bayesian decision theory can be used to drive decisions within the development of new technologies aiding research screening, technology characteristics, and employment optimization. The selection of a specific application of technology leads to the definition of the decision scenario within the Value of Information framework. Technological performance characteristics are therefore optimized towards the specific implementation minimizing development cost and enhancing technological efficiency. This paper presents the application of a multi-scenario decision value quantification for the development of a new vibration-based monitoring technology. Two emergency management decision scenarios, corresponding to the scour and seismic hazards, are selected to optimize technology charcteristics. Four new metrics based on the Value of Information are provided to support the VBM technology market diffusion.
Publisher Copyright: © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Innovation; Integrity management; Structural health monitoring; Value of information; Vibration-based monitoring